DESAIN WAYANG PADA BATIK RAKYAT EKS-KARESIDENAN SURAKARTA YANG BERNILAI JUAL DAN BERMUATAN EDUKATIF - Sugeng Nugroho; Muh. Arif Jati Purnomo; Kuwato Kuwato (Institut Seni Indonesia Surakarta, 2013)
This study tried to elevate wayang as a folk pattern design. It is intended to remind people of thevalues of local wisdom implicitly written in wayang figures. Folk’s batik was chosen as the producttarget, based on the consideration that the pattern in it is highly varied; depend on the culturalbackground of each region. This study is also intended to elevate the economy of the batik crafternot only depend on the brokers, the expectation is to develop national character and to improvethe welfare of common people. The research is targeting the batik centrals in six districts of ex-Surakarta region: Boyolali, Sukoharjo, Karanganyar, Wonogiri, Sragen, and Klaten. The result ofthe research shows that Sukoharjo, Karanganyar, Wonogiri, Sragen, and Klaten have clusters ofbatik crafters that sufficient enough to be empowered. Wayang designs on batik patterns in the sixregion showed less commercial value since the shapes and colorings were unattractive, hence,the researcher tried to create a wayang design that is worth selling and contain educational content.